Gastropericardial fistula: A rare etiology of chest pain. Issue 2 (March 2018) - Ghalem, Amine; Berrajaa, Mehdi; Ahsayan, Kamal; Aabdi, Mohammed; Boutahar, Imane; Skiker, Imane; Housni, Brahim; Ismaili, Nabila; Ouafi, Noha El
Gastropericardial fistula is an abnormal communication between the stomach and the pericardium. It is a rare, life-threatening condition that has numerous etiologies. We report the case of a 53-year-old male patient, with a history of wedge resection for gastrointestinal stromal tumor, who presented to the emergency department for epigastric and chest pain along with lethargy leading to the uncommon diagnosis of gastropericardial fistula with pneumopericardium. Through this case, we would like to draw clinicians' attention to gastropericardial fistula as a differential diagnosis in patients presenting for epigastric and/or chest pain with a history of esophagogastric surgery, emphasizing on the key role of computed tomography in this regard, and underscore the management basics of this unusual condition.